Autophosphorylation and Pin1 binding coordinate DNA damage-induced HIPK2 activation and cell death - Bitomsky, Nadja; Conrad, Elisa; Moritz, Christian; Polonio-Vallon, Tilman; Sombroek, Dirk; Schultheiß, Kathrin; Glas, Carolina; Greiner, Vera; Herbel, Christoph; Mantovani, Fiamma; Sal, Giannino del; Peri, Francesca; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Excessive genome damage activates the apoptosis response. Protein kinase HIPK2 is a key regulator of DNA damage-induced apoptosis. Here, we deciphered the molecular mechanism of HIPK2 activation and show its relevance for DNA damage-induced apoptosis in cellulo and in vivo. HIPK2 autointeracts and site-specifically autophosphorylates upon DNA damage at Thr880/Ser882. Autophosphorylation regulates HIPK2 activity and mutation of the phosphorylation-acceptor sites deregulates p53 Ser46 phosphorylation and apoptosis in cellulo. Moreover, HIPK2 autophosphorylation is conserved between human and zebrafish and is important for DNA damage-induced apoptosis in vivo. Mechanistically, autophosphorylation creates a binding signal for the phospho-specific isomerase Pin1. Pin1 links HIPK2 activation to its stabilization by inhibiting HIPK2 polyubiquitination and modulating Siah-1-HIPK2 interaction. Concordantly, Pin1 is required for DNA damage-induced HIPK2 stabilization and p53 Ser46 phosphorylation and is essential for induction of apotosis both in cellulo and in zebrafish. Our results identify an evolutionary conserved mechanism regulating DNA damage-induced apoptosis.
Gesehen am 26.11.2020